Influence Breast Care Massage Methods To Increase Production Oketani mother's milk (ASI) On Mother Post Partum In Puskesmas Gunungsitoli-Nias: Influence Breast Care Massage Methods To Increase Production Oketani mother's milk (ASI) On Mother Post Partum In Puskesmas Gunungsitoli-Nias - Jernihati Krisniat Harefa; Anita Deborah Anwar; Tania Novi; Hidayat Wijayanegara; Leri Septiani; Herry Garna (Journal of Midwifery and Nursing, 2020)
Oketani massage method can stimulate the pectoral muscle strength mayoruntuk increase milk production and makes the breasts become soft and elastic, making it easier for the baby to suckle. Breast care massage method Oketani this method does not provide pain and discomfort to the mother's breast that is different from the conventional massage. This study aimed to analyze the effect of breast care massage Oketani method to increase milk production in postpartum mothers with indicators of infant weight gain. The method used is quasi-experimental with two group design approach pretest posttest control group design with a sample of 82 mothers postpartum primiparous spontaneous and have a baby. The experiment was conducted in Puskesmas Kota Gunung Sitoli-Nias May to July 2019. Sampling consecutive sampling to obtain each 41 respondents mothers and babies the treatment group and the control group. Variable Methods breast care and breast care massage Oketani conventionally measured by observation sheet, whereas to measure the milk production with the baby weighing indicator. Analysis of the characteristics of respondents were tested using the chi-square test, the mean differences with the Mann-Whitney test, and the difference between the intervention and control by Friedman test. The results showed an average weight infants in the intervention group showed an increase Oketani massage method of infant weight at day 14 as much as 3.35% of birth weight whereas the control group declined 1.3% of birth weight. The result of the difference between the two groups showed no significant difference between before and after the intervention, p = 0.000. In conclusion, there is the effect of breast care massage Oketani method to increase milk production (milk) in the mother post partum.